2006
DOI: 10.1103/physrevb.73.140507
|View full text |Cite
|
Sign up to set email alerts
|

Super-weakly coupled superconductivity in ultrathin superconductor–normal-metal bilayers

Abstract: Tunneling measurements of the temperature dependence of the electronic density of states (DOS) of ultrathin bilayers of Pb and Ag reveal that their superconducting energy gap, ∆(T ), evolves similarly to BCS predictions despite the presence of a large anomalous DOS at the Fermi energy that persists as T → 0. The gap ratio,k B Tc , systematically decreases more than 20% below the BCS universal value of 3.52 in bilayers with the lowest superconducting transition temperatures, T c ; a behavior we deem super weakl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
(51 reference statements)
2
18
0
Order By: Relevance
“…48,49 A straightforward realization of inhomogeneous coupling is in disordered superconductor-normalmetal ͑SN͒ bilayer thin films. In a homogeneous bilayer SN with thickness smaller than the coherence length , meanfield analysis yields that T c and the energy gap E g of the system are determined by the averaged coupling constant [50][51][52] …”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…48,49 A straightforward realization of inhomogeneous coupling is in disordered superconductor-normalmetal ͑SN͒ bilayer thin films. In a homogeneous bilayer SN with thickness smaller than the coherence length , meanfield analysis yields that T c and the energy gap E g of the system are determined by the averaged coupling constant [50][51][52] …”
Section: Summary and Discussionmentioning
confidence: 99%
“…41,48,49 Interestingly, these studies found a broadening of the BCS peak and also a subgap density of states. 6,23,25,26,28,48 Of particular interest to us is the work in Ref.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Numerous STM experiments have shown that the DOS broadening can be significant, particularly in thin films and bilayers [37][38][39] . The subgap states have been attributed to inelastic scattering of quasiparticles on phonons 9,40 , Coulomb correlations 41 , anisotropy of the Fermi surface 42 , inhomogeneities of the BCS pairing constant 43 , magnetic impurities 31 , spatial correlations in impurity scattering 31,44 , or diffusive surface scattering.…”
Section: Introductionmentioning
confidence: 99%